Efficacy, safety, and therapeutic drug monitoring of polymyxin B sulfate and colistin sulfate in critically ill patients: a real-world retrospective study - Zhang, Yijing; Wang, Chuhui; Chen, Jiaojiao; Bai, Chuqi; Sun, Dan; Qiu, Yulan; Teng, Mengmeng; Dong, Yalin (Frontiers in Pharmacology, 2025)
BackgroundPolymyxin B sulfate (PBS) and colistin sulfate (CS) are the last-line treatments for infections caused by multidrug-resistant Gram-negative bacteria, but their efficacy and safety have not been validated. The aims of the current study were to (1) determine their efficacy and safety among critically ill patients and the influencing factors, and (2) determine the relationships of drug exposure with efficacy and safety, to provide evidence for the precision dosing.MethodThis retrospective study included 100 critically ill patients treated with PBS and 80 treated with CS. The efficacy outcomes were clinical efficacy and 30-day mortality, while the safety indicator was acute kidney injury (AKI) incidence.ResultThere was no significant difference between the two drugs in clinical efficacy, 30-day mortality, or overall AKI incidence, but the incidence of stage 3 AKI was significantly higher in the PBS cohort than the CS cohort. Therapeutic drug monitoring (TDM) and trough concentration (Cmin) were significantly associated with clinical efficacy and AKI in both cohorts. Classification and regression tree analysis revealed that Cmin values of ≥0.91 mg/L for PBS and Cmin ≥ 0.53 mg/L for CS were associated with higher clinical efficacy.ConclusionThere is basically no significant difference in the efficacy and safety of PBS and CS. TDM can significantly improve the clinical efficacy of both drugs and reduce the incidence of AKI. TDM is therefore recommended to improve the clinical efficacy while reducing the adverse reactions.